L’ éducation physique et les sports (Fiep Bulletin - online, 2015)
Edited by the council for cultural cooperation of the council of Europe, this work gives a clear outlook on physical educational and sports in 18 European countries. It has therefore a great interest thanks to the information supplied on governamental, provincial, municipal and private organization which deal with the problem, specially on the training of teachers, etc.